STRATEGI PENGEMBANGAN OBYEK WISATA AIR TERJUN SANGGILIPAN DI KECAMATAN DELANG KABUPATEN LAMANDAU : Antonius Triyadi1, Yuni Setiawati 2 - Admin JHT (HUTAN TROPIKA, 2016)
ABSTRACT This research aimed to identify the driving factors and obstacles as well as analyzing strategic options might be taken by Lamandae, Central Kalimantan Province in order to manage Sanggilipan waterfall at the site. The research was carried out at Sanggilipan waterfall in Jojabo Hulu Village, Delang sub-District, Lamandau District. The research was conducted using SWOT as its analytical tool, and based on the fact that Sanggilipan waterfall has plenty of natural potential but has not been optimally utilized, this research proposes SO (Strength and Opportunity) as alternative strategy for its further development. Therefore, the development of Sanggilipan waterfall should consider the Strength and utilize the opportunities it has. Keywords: Strategic options, Sanggilipan waterfall, SWOT analysis